1999
DOI: 10.1097/00007890-199910270-00012
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Hepatitis C Virus-Associated Membranoproliferative Glomerulonephritis After Liver Transplantation

Abstract: Membranoproliferative glomerulonephritis does not constitute an absolute contraindication for liver transplantation alone; combined liver-kidney transplantations are reserved for patients with end-stage kidney failure. Proteinuria is reversed after liver transplantation, and recurrence seems to be associated with severe hepatitis C virus hepatic allograft disease relapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…The specific renal disease, along with the volume of glomerular and interstitial scar determined by renal biopsy, clinical characteristics, past and/or probable future treatment responses, likeli- hood of spontaneous disease remission, and, importantly, the probability of improved renal function after correction of hepatic failure, are all considered by the nephrologist in an attempt to predict the onset of renal failure. 13,22,36 A discussion of the development of ESRD through the process of fibrosis follows: clinical characteristics associated with progressive renal disease and the probability of spontaneous remission of primary renal diseases are listed in Table 2. Progression of renal disease to end stage has been predicted most accurately histologically by the degree of interstitial fibrosis, although the presence of myofibroblasts (cells that generate excessive volumes of interstitial matrix), degree of glomerulosclerosis, and some disease-specific characteristics also may be predictive (Fig.…”
Section: Progression Of Renal Disease: Pathogenesismentioning
confidence: 99%
“…The specific renal disease, along with the volume of glomerular and interstitial scar determined by renal biopsy, clinical characteristics, past and/or probable future treatment responses, likeli- hood of spontaneous disease remission, and, importantly, the probability of improved renal function after correction of hepatic failure, are all considered by the nephrologist in an attempt to predict the onset of renal failure. 13,22,36 A discussion of the development of ESRD through the process of fibrosis follows: clinical characteristics associated with progressive renal disease and the probability of spontaneous remission of primary renal diseases are listed in Table 2. Progression of renal disease to end stage has been predicted most accurately histologically by the degree of interstitial fibrosis, although the presence of myofibroblasts (cells that generate excessive volumes of interstitial matrix), degree of glomerulosclerosis, and some disease-specific characteristics also may be predictive (Fig.…”
Section: Progression Of Renal Disease: Pathogenesismentioning
confidence: 99%
“…Hepatitis C virus (HCV) infection complicates clinical outcome in liver and renal allografts (1). Besides its important contribution to chronic liver disease, HCV infection is also a relevant cause of de novo immune‐mediated glomerulonephritis in both kidney and liver transplantation (2,3). In a previous work we demonstrated that de novo type I membranoproliferative glomerulonephritis (MPGN) is mediated by a very low level of nephritogenic type II cryoglobulins containing HCV‐RNA (4).…”
Section: Introductionmentioning
confidence: 99%
“…After renal transplantation, despite temporary improvements in creatinine plasma levels, proteinuria persisted and allograft biopsy was consistent with recurrence of his MPGN. HCV kidney disease is more commonly seen in transplant (both renal or hepatic) recipients than in the native kidneys of HCV-positive individuals (9,10). This is thought to be a result of higher HCV RNA levels secondary to the immunosuppression, which in turn leads to increased viral complex deposition in the glomerulus (11).…”
Section: Discussionmentioning
confidence: 99%